For an "Observatory on Critical Editions". Chronicle of the seminar of 13 September 2017 (Prassi Ecdotiche della Modernità Letteraria, 2017)
The seminar For an "Observatory on Critical Editions" - the 11th cycle of Prassi ecdotiche, philological seminars dedicated to the memory of Giovanni Orlandi - was held during the afternoon of September 13th, 2017 at the University of Milan. It was introduced and coordinated by Paolo Chiesa (University of Milan), and included, as speakers, Lino Leonardi (University of Siena - OVI CNR, Florence), Paolo Trovato (University of Ferrara) and Giuseppe Ucciardello (University of Studies of Messina).In the introduction to the works, Paolo Chiesa presented the research group promoter of the "Observatory", recalling how the project was born as a research of the Department of Literary, philological and linguistic studies of the University of Milan, which accepted and funded it on November 14th, 2016. Chiesa has therefore enhanced the interdisciplinary nature of the research group that initiated the initiative, being composed of five scholars Alberto Cadioli, the same Paolo Chiesa, William Spaggiari, Stefano Martinelli Tempesta and Roberto Tagliani), belonging them all to the same department but each one to a different sector. All these sectors of study, from the chronological point of view, range from classical philology to studies of contemporary Italian literature.